Visualizing thrombosis to improve thrombus resolution. Issue 1 (6th January 2021) - Weisel, John W.; Litvinov, Rustem I.
Abstract: The severity, course, and outcomes of thrombosis are determined mainly by the size and location of the thrombus, but studying thrombus structure and composition has been an important but challenging task. The substantial progress in determination of thrombus morphology has become possible due to new intravital imaging methodologies in combination with mechanical thrombectomy, which allows extraction of a fresh thrombus from a patient followed by microscopy. Thrombi have been found to contain various structural forms of fibrin along with platelet aggregates, leukocytes, and red blood cells, many of which acquire a polyhedral shape (polyhedrocytes) as a result of intravital platelet‐driven contraction. The relative volume fractions of thrombus components and their structural forms vary substantially, depending on the clinical and pathogenic characteristics. This review summarizes recent research that describes quantitative and qualitative morphologic characteristics of arterial and venous thrombi that are relevant for the pathogenesis, prophylaxis, diagnosis, and treatment of thrombosis.